Indecent exposure eaudiobook - Woods, Stuart (Stone Barrington, 2017)
In this action-packed adventure from #1 New York Times  bestselling author Stuart Woods, Stone Barrington learns that privacy is hard to come by when you’re one of the rich and mighty. As an eligible bachelor, man-about-town, and mover in the highest social echelons, Stone Barrington has always been the subject of interest and gossip. But when he’s unwittingly thrust into the limelight, he finds himself scrambling to take cover. Before too long Stone’s fending off pesky nuisances left and right, and making personal arrangements so surreptitiously it would take a covert operative to unearth them. Unfortunately, Stone soon discovers that these efforts only increase the persistence of the most troublesome pests...and when he runs afoul of a particularly tenacious lady, he’ll be struggling to protect not just his reputation, but his life.